Komunikasi Interpersonal Pengasuh Pada Anak Asuh di Panti Asuhan Amal Wanita (An-Nur) Depok - Taufik Paturohman; Muhammad Sahrul (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Communication is the process of exchanging and sharing information that plays a role as a medium in conveying information and a tool to influence others. One type of communication that is often used is interpersonal communication, because it is done face-to-face directly and using smartphones that are considered effective for persuading others, as well as carried out by caregivers at the An-Nur Women's Charity Home. This research aims to find out how to apply the elements of interpersonal communication media used, how to achieve the goals of interpersonal communication, and the driving and inhibiting factors of interpersonal communication. Methods used in this study include qualitative research with a case study approach. Data were collected through in-depth interviews, observations, and documentation from various informants. The results of the analysis show that the interpersonal communication process provided by caregivers includes material about religion, education, guidance, reprimands, advice, questions, storytelling, motivation, and solutions. Additionally, there is a closeness in interpersonal communication between caregivers and children, formed through listening, opening up to each other, sharing stories, understanding messages, and making caregivers both friends and parents. Empathetic, consistent, and attentive communication from the caregiver significantly contributes to the formation of self-confidence, social skills, independence, and responsibility in foster children. Furthermore, a caregiver with strong interpersonal relationships creates a comfortable and supportive environment for children to develop optimally. Open and supportive interpersonal communication helps the child feel valued, heard, and cared for, which contributes to the development of foster children in line with expectations.